The performance of Kempas and Keruing in structural finger jointing / Suhaimi Muhammed and Wan Mahmood Wan Abdul Majid - Muhammed, Suhaimi; Wan Abdul Majid, Wan Mahmood (Universiti Teknologi MARA Pahang, Jengka, 1999)
Structural finger jointing were made from Kempas (Koompassia malaccensis), and Keruing (Dipterocarpus spp.) using three finger length profiles (11, 12, 13 mm) and were tested in bending and tension to assess and compare their finger joint strength. The adhesive used was cold setting resorcinol formaldehyde (RF). The results showed that finger jointed Kempas has strength properties superior to Keruing and met the requirement as specified in the Malayan Grading Rules stress grade for solid timber only when finger length of greater than 11 mm was used, while Keruing failed to meet the requirement.